SOCIAL ENTREPRENEURSHIP IN ENVIRONMENTAL PROJECTS - OLGA ALEXANDROVNA Ryabova; ALEXANDR VLADIMIROVICH Meshankin (Мир новой экономики, 2018)
This article discusses the principles of social entrepreneurship, which can be used in the implementation of environmental initiatives that require long-term approach and the application of business arrangements in low profitability of environmental projects.The paper highlights the motivation and incentives of environmental behavior of the entrepreneur, defines the relationship between quality of life and ecological culture of society.The authors propose to support social entrepreneurs involved in the solution of environmental problems of the society instead of exploiting the environmental image of the company. Unlike ineffective one-time environmental activities of corporate business the mechanisms of social business can increase the environmental effect and maintain it on a due level.The article compares the philanthropy, traditional and social entrepreneurship, it also reflects on the principles of the social business.The relevance of social entrepreneurship to the environmental sector is illustrated with the ongoing projects, as well as new ideas that, according to experts, have great potential for success.